PENGARUH ENDORPHINE MASSAGE TERHADAP KECEMASAN PASIEN PRE SECTIO CAESAREA DI RSUD ENGKU HAJI DAUD - Arum Dwi Anjani; Devy Lestari Nurul Aulia; Risqi Utami; Maya Sumanti (JOMIS (Journal of Midwifery Science), 2022)
Riskesdas 2018 data from Riau Archipelago Province shows that the most Sectio Caesarea deliveries occur to mothers with an age range of 45-49 years (27.66%), education D1/D2/D3/PT (36.95%), most occupations are private employees (42.30%), and live in urban areas (24.6%). When preparing for a cesarean section, the patient will be faced with the operation process, the safety of the baby, and himself. Untreated preoperative anxiety can lead to complications that result in surgery delays. Therefore, anxiety in preoperative caesarean section mothers must be overcome, one of which is endorphin massage intervention. This study aims to determine the effect of endorphine massage on the anxiety level of pre Sectio Caesaria mothers. The study used a quasi-experimental method with a pre-post-test design (one group - pre-test - post-test design). The study was conducted in October 2020-February 2021 at Engku Haji Daud Tanjung Uban Hospital. The study population was pregnant women with pre sectio caesarea 20 respondents. The sample uses total sampling. The results showed that the average anxiety before the endorphine massage intervention was 21.85, while after the intervention was 12.85, this result showed the difference in the average anxiety score for pre-cesarean mothers was 9. The results of the Wilcoxon test statistic test showed the p < 0.05, the conclusion is that there is an effect of endorphine massage on anxiety levels in pre Sectio Caesaria mothers. It is recommended for mothers to be able to apply endorphine massage techniques to reduce anxiety, it can also be done at home.